Contradiction and Legal Transformation in the Shift of the Correctional System from Retributive to Social Reintegration in Indonesia - Purnomo, Didik (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2025)
The transformation of Indonesia’s correctional system from a retributive approach that emphasizes punishment and isolation toward social reintegration through Law Number 22 of 2022 on Corrections has generated normative contradictions with the previous law oriented toward retribution. This transition faces structural obstacles such as prison overcrowding and budgetary constraints, yet it is driven by policy reforms aimed at achieving the successful reintegration of inmates. This study aims to understand the root causes of legal issues, trace the regulatory development, and examine various crucial aspects that may function as barriers or, on the other hand, encourage the implementation of the reintegration model. This research analyzed the legal transformation of the correctional system from retributive to reintegrative in Indonesia through a normative juridical and historical approach. It utilized primary data from legislation, secondary data from literature, tertiary data from official publications, and case studies, which were analyzed using content analysis and a descriptive-analytical method. The research results indicate that the transformation of Indonesia’s correctional system toward a rehabilitative and restorative paradigm through Law No. 12/1995, Law No. 22/2022, and the National Criminal Code No. 1/2023 remains hindered by overcrowding, budget limitations, and social stigma. Therefore, policy synergy, institutional capacity building, and a shift in social paradigms are required to realize restorative justice, human rights protection, and sustainable inmate reintegration